DISSEMINATION OF METHODOLOGICAL ASSISSTANCE FOR TECHNOLOGY SUBJECTS TEACHERS - BANESZ, Gabriel (Trends in education, 2012)
The aim of this paper is to shift the SRDA (Slovak research and development agency) project called Dissemination of methodological assisstance for technology subjects teachers. The project aim is to adapt EduTech Portal Website for the target group of teachers of technical subjects focusing on the Czech Republic.
Keywords: EduTech Portal; methodological assisstance; technology edutacion.